Latitudinal variation in plant chemical defences drives latitudinal patterns of leaf herbivory. Issue 7 (23rd November 2017) - Moreira, Xoaquín; Castagneyrol, Bastien; Abdala‐Roberts, Luis; Berny‐Mier y Teran, Jorge C.; Timmermans, Bart G. H.; Bruun, Hans Henrik; Covelo, Felisa; Glauser, Gaétan; Rasmann, Sergio; Tack, Ayco J. M.
Abstract : A long‐standing paradigm in ecology holds that herbivore pressure and thus plant defences increase towards lower latitudes. However, recent work has challenged this prediction where studies have found no relationship or opposite trends where herbivory or plant defences increase at higher latitudes. Here we tested for latitudinal variation in herbivory, chemical defences (phenolic compounds), and nutritional traits (phosphorus and nitrogen) in leaves of a long‐lived tree species, the English oak Quercus robur . We further investigated the underlying climatic and soil factors associated with such variation. Across 38 populations of Q. robur distributed along an 18° latitudinal gradient, covering almost the entire latitudinal and climatic range of this species, we observed strong but divergent latitudinal gradients in leaf herbivory and leaf chemical defences and nutrients. As expected, there was a negative relationship between latitude and leaf herbivory where oak populations from lower latitudes exhibited higher levels of leaf herbivory. However, counter to predictions there was a positive relationship between leaf chemical defences and latitude where populations at higher latitudes were better defended. Similarly, leaf phosphorus and nitrogen increased with latitude. Path analysis indicated a significant (negative) effect of plant chemical defences (condensed tannins) on leaf herbivory, suggesting that the latitudinal gradient in leaf herbivory was driven by an inverse gradient in defensive investment. Leaf nutrients had no independent influence on herbivory. Further, we found significant indirect effects of precipitation and soil porosity on leaf herbivory, which were mediated by plant chemical defences. These findings suggest that abiotic factors shape latitudinal variation in plant defences and that these defences in turn underlie latitudinal variation in leaf herbivory. Overall, this study contributes to a better understanding of latitudinal variation in plant–herbivore interactions by determining the identity and modus operandi of abiotic factors concurrently shaping plant defences and herbivory.